Própolis vermelha na angiogênese em bolsa jugal de hamster submetidos a implante de esponja - Melo, Nayanna de Oliveira Ramos (2018)
Angiogenesis consists in formation of new blood vessels from other vessels already existing. It is a process that can occur in a pathological way, acting in the progression of several in-flammatory diseases such as psoriasis, endometriosis, among others. This work aimed to evaluate the effects of red propolis on inflammatory angiogenesis in a model of sponge im-plant in a hamster cheek pouch. We used 48 animals divided into 8 groups. Groups I, II, III and IV (were treated with red propolis 100 mg / 5 ml / kg - celecoxib 20 mg / kg - gum arabic 1% AP 5 ml / kg - water 5 ml / kg, respectively) for 15 days before and 10 days after the sponge implant. Groups V, VI, VII and VIII (were treated with red propolis - 100 mg / 5 ml / kg - celecoxib - 20 mg / kg -Arabic gum AP 1% -5 ml / kg -water- 5 ml / kg, respectively) for 10 days from the sponge implant. Angiogenesis was evaluated by determining the mean vas-cular area (AVM) in pixels (px) and in percentage terms (%). In the study of groups I, II, III and IV, no statistically were found significant differences between the groups for AVM (px) (F = 2.6712; p = 0, 0752) nor for AVM (%) values (F = 2.6711, p = 0, 0752). In the study of groups V, VI, VII and VIII, there were no statistically significant differences between the groups or AVM (px) values (F = 0.6255; p = 0, 6069) or AVM (%) values (F = 0.6255, p = 0, 6069) and no significant statistical differences were found between the experimental groups and their controls. In the analysis of inflammation (qualitative), there was a decrease of mast cell in group I comparing to group IV (control) with a significant statistical difference (p = 0, 013); there was a decrease of blood vessels number in group I comparing to group IV (control) with signifi-cant statistical difference (p = 0, 007); there was an increase of macrophages number of group I comparing to the other groups (II, III and IV) with significant statistical difference (p = 0, 001). Red propolis inhibited angiogenesis when administered prior to and continuously after implantation. Red propolis has immunomodulatory effects on inflammatory cells (mast cells and macrophages). Keywords: Angiogenesis Inhibitors. Propolis. Inflammation. Mesocricetus.